2002
DOI: 10.1190/1.1468596
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal offset‐dependent attributes applied to fracture detection in a carbonate reservoir

Abstract: Offset-dependent attributes-amplitude versus offset (AVO) and frequency versus offset-are extracted from 2-D P-wave seismic data using the multiple signal classification technique. These attributes are used to detect fracture orientation in a carbonate reservoir located in the Maporal field in the Barinas basin of southwestern Venezuela. In the fracture normal direction, P-wave reflectivity is characterized by a large increase of amplitude with offset (large positive AVO gradient) and a large decrease of frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The azimuthal AVO (AVOaz) properties of reflected PP waves have been used to identify fracture orientation (e.g. Shen et al, 2002). However, the effective media model (EMM) is only valid for media with fractures that are small relative to the seismic wavelength (e.g., Lynn, 2004, Liu et al, 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The azimuthal AVO (AVOaz) properties of reflected PP waves have been used to identify fracture orientation (e.g. Shen et al, 2002). However, the effective media model (EMM) is only valid for media with fractures that are small relative to the seismic wavelength (e.g., Lynn, 2004, Liu et al, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting seismic reflections from the top and bottom of a fractured reservoir will display amplitude variations with offset and azimuth (AVOA). In recent years much progress has been made analyzing AVOA effects (e.g., Sayers and Rickett, 1997;Perez et al, 1999;Jenner, 2002;Shen et al, 2002;Hall and Kendall, 2003;Lynn and Cox, 2003;Minsley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A 3D finite difference method is used to simulate wave propagation through a simple fractured reservoir which is modeled as a single horizontal layer containing parallel, evenly-spaced fractures. Previous work has shown that the finite difference method is accurate over a wide range of scattering regimes and can account for all converted waves and their interactions (Shen et al, 2002). Synthetic seismograms are generated along transects perpendicular and parallel to the fracture orientation and spectral characteristics of the wavefield scattered from the fracture zones are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Others have looked at shear wave data for fracture analysis (Lynn et al, 1995;Gaiser et al, 2002). Shen et al (2002) used numerical experiments and field data from a fractured reservoir in Venezuela to demonstrate the advantages of using attributes based on frequency variations with offset and azimuth (FVOA) in addition to AVOA based attributes to further constrain the interpretation of parameters related to the presence of vertically aligned fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation